The Effect of Customer Relationship Management and Service Innovation on Customer Loyalty Through Customer Satisfaction Case Study: PT. Sayap Mas Utama - Subandi Subandi; Maulidin Wahid; M. Wisanggeni Ariohadi; Stefanus Berhand Putra Aryawan (Jurnal Ilmu Multidisiplin, 2025)
With customer satisfaction acting as a crucial mediating variable, this study attempts to learn a great deal about CRM variables and service innovation at PT. Sayap Mas Utama in order to promote customer loyalty. Our study's focus is at Sayap Mas Utama, PT. This research employs a survey methodology and a quantitative approach, incorporating participants from a range of industrial sectors. Questionnaires that have been verified for validity and reliability were used to gather data. Multiple regression approaches and path analysis were employed in the data analysis process to examine the direct and indirect correlations between the variables under investigation. The results showed that CRM and service innovation have a significant positive effect on customer satisfaction. In addition, customer satisfaction, as a mediating variable, is proven to play a key role in the relationship between CRM and customer loyalty and between service innovation and customer loyalty. This study concludes that to increase customer loyalty, companies need to focus on two main things, namely, building strong relationships with customers through CRM and continuing to innovate in the services offered. Customer satisfaction is the key to achieving these goals.